The Role of Firm Size as a Moderating Variable on Special Relationship Transactions, Modal Intensity, and Profitability Towards Effective Tax Rate - Lukman Hakim; Daljono Daljono (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The purpose of this study is to examine the interactions between a number of variables that affect the effective corporate tax rate (ETR), including special transaction relationship—in this example, affiliate debt—modal intensity, and profitability—using the size of the company as a moderating variable. Panel data from 41 manufacturing businesses listed on the Indonesian Stock Exchange for the years 2017 through 2021 was used to implement the strategy. Our findings demonstrate that the impact of special relationship transactions on effective tax rates is neither affected nor changed by corporation size. According to data processing findings, a company's size can both adversely reduce the impact of modal intensity on the effective tax rate and positively moderate the impact of modal intensification on the effective tax rate. These results, in our opinion, will be helpful to governments when deciding on fiscal policies as well as to businesses when deciding where to locate and make investments in these nations. This study, in our opinion, is a significant contribution to the literature since it takes into account new factors, including institutional and business-related factors, that were not jointly taken into account in other studies on the determinant effective tax rate.